Validation of the European Prospective Investigation into Cancer (EPIC) FFQ for use among adults in Lebanon. Issue 13 (14th September 2021) - Khaled, Karim; Hundley, Vanora; Bassil, Maya; Bazzi, Mira; Tsofliou, Fotini
Abstract: Objective: To validate the European Prospective Investigation into Cancer (EPIC) FFQ in Lebanon. Design: Validation of the EPIC FFQ was done against three 24-h recalls (24-HR). Unadjusted and energy-adjusted correlations, Bland–Altman plots and weighed kappa statistics were used to assess the agreement between the two methods. Setting: Lebanon. Participants: 119 adults (staff and students) at a Lebanese University. Results: Good unadjusted and energy-adjusted correlation coefficients were found between data from the two methods which ranged from –0·002 (vitamin A) to 0·337 (carbohydrates) and were all statistically significant except for vitamin D, vitamin E, vitamin A, Se and niacin. Slight/fair agreement was reported through weighed kappa estimates for unadjusted data ranging from –0·05 (vitamin C) to 0·248 (Mg) and for energy-adjusted data ranging from –0·034 (vitamin A) to 0·203 (P). Individuals were categorised into exact and adjacent quartiles with an average of 78 % for unadjusted data and 70 % for energy-adjusted data, indicating a very good agreement between the EPIC FFQ and the average of the 24-HR data. The visual inspection of the Bland–Altman plots revealed an overestimation of energy, carbohydrates, protein and fat intakes by the FFQ method. Conclusion: Overall, when all tests were taken into consideration, the current study demonstrated an acceptable agreement of the EPIC FFQ with the 24-h dietary recall method and significantly good correlations between dietary intakes. Therefore, the EPIC FFQ can be considered a valid tool for assessing diet in epidemiological studies among Lebanese adults.